A stream‐to‐sea experiment reveals inhibitory effects of freshwater residency on organic‐matter decomposition in the sea. Issue 3 (17th May 2022) - Frainer, André; Tiegs, Scott D.
Abstract: One billion tons of carbon are annually transported to the global ocean, and the fate of this carbon hinges not only on marine processing rates, but also on freshwater processing during downstream transport. Using a cotton‐strip assay, we assessed the decomposition of organic matter in marine and freshwater sites and simulated its downstream transport from freshwater to the sea by translocating cotton strips approximately half‐way through the freshwater incubation period. We observed faster decomposition in the sea relative to the stream and interestingly, an inhibitory effect of stream incubation on subsequent decomposition in the sea. Total nitrogen content and ∂ 15 N in the cotton strips were both greater in the strips incubated entirely in the sea, suggesting greater microbial activity in the marine habitat. Our results lend needed insights into global carbon cycling, the factors that govern organic‐carbon processing, and highlight the importance of connections that exist among some of Earth's major ecosystems.